Endurance ability characteristics of professional sportsmen - Rozenstoka, S. (Journal of Human Sport & Exercise, 2012)
Cycling and kettlebell sport are cyclic kinds of sport. For sport achievement is important the development of endurance ability. In kettlebell sport high performance is based on the strength endurance. One of the conditions for success in competition is sportsman`s high aerobic and anaerobic capacity (Lescinskis, 2010). Complex cardiopulmonary exercise testing allows for simultaneous study of the responses of the cardiovascular and pulmonary systems to a stated physical load stress. There is direct correlation between physical work capacity and functional ability of the body. Determining aerobic and anaerobic ability is equally important for estimating functional abilities of the body. The performance of muscular work requires physiological responses of the body systems to be coupled in order to increase metabolic rate. The aim of the study is to assess the difference of basic parameters of physical work capacity during physical load between professional cyclists and kettlebell lifters. Physiological testing of sportsmen as an integral part of professional sport now can show the physical work capacity and the functional ability of the body. Regular endurance load causes one of the adaptation changes of cardiovascular system with decreasing of heart rate during the rest and load. Relative maximal physical work capacity is relevantly higher for professional cyclists for about 27% than it is for kettlebell lifters. Aerobic and anaerobic thresholds increase in regular endurance trainings. The body clearly has an upper limit for oxygen uptake at present state of condition, physical training of the body and person`s practice regime. Maximal oxygen uptake is relevantly higher about 24% for professional cyclists than it is for the kettlebell lifters.